Vacuoles in Bryophytes: Properties, Biogenesis, and Evolution - Liu, Hao-ran; Shen, Chao; Hassani, Danial; Fang, Wan-qi; Wang, Zhi-yi; Lu, Yi; Zhu, Rui-liang; Zhao, Qiong (Frontiers in Plant Science, 2022)
Vacuoles are most conspicuous organelles in plants for their indispensable functions in cell expansion, solute storage, water balance etc. Extensive studies on angiosperms have revealed that a set of conserved core molecular machineries orchestrate the formation of vacuoles from multiple pathways. Usually, vacuoles in seed plants are classified into protein storage vacuoles and lytic vacuoles for their distinctive morphology and physiology function. Bryophytes represent early diverged non-vascular land plants, and are of great value for better understanding of plant science. However, knowledge about vacuole morphology and biogenesis are far less characterized in bryophytes. In this review, first we summarize known knowledge about the morphological and metabolic constitution properties of bryophytes’ vacuoles. Then based on known genome information of representative bryophytes, we compared the conserved molecular machinery for vacuole biogenesis among different species including yeast, mammals, Arabidopsis and bryophytes and listed out significant changes in terms of the presence/absence of key machinery genes which participate in vacuole biogenesis. Finally, we propose the possible conserved and diverged mechanism for biogenesis of vacuoles in bryophytes compared with seed plants.